Review on Nilibhringadi Taila: An Effective Keshya Medication - Vashishtha; Neha Meena; Mohar Pal Meena (AYUSHDHARA, 2023)
One third of the population, including both men and women, experience hair problems, making it one of the most prevalent issues in the world. Both men and women in India are very sensitive about their hair. Numerous reasons, including hormone imbalances, stress, rising work pressure, poor dietary practises, and excessive use of chemical cosmetics, have contributed to a rise in cases of hair diseases and hair problems. Losing one's hair can be embarrassing and detrimental to one's confidence and self-esteem. Ayurveda provides some successful external hair management therapies. The pharmaceutics and therapeutics of Ayurvedic dose forms are quite specialised. Sneha Kalpana is a collection of medicated Taila and Ghrita that treat a wide variety of diseases in people of all ages. Sneha kalpas produced by Ayurvedic pharmaceutics are broadly utilised for both cosmetic and therapeutic purposes. It is the only Kalpana used in all four ways that these formulations can be administered: Pana, Abhyanga, Nasya, and Basti. In Ayurveda, hairs are referred to as Kesha, and medications that are effective for hairs are referred to as Keshya medications. In this article we have made an effort to describe the formulation Nilibhringadi Taila which is described in Sahasrayogam and Chikitsa Manjari. Nilibhringadi Taila is an Ayurvedic and herbal oil, which is useful to improve the quality of hair, to treat split hairs, premature greying and baldness. All ingredients in formulation are best hair growth promoters. It is widely used and prescribed formulation in India. Here not much more work has been done on this formulation. So we are trying to review this formulation for further knowledge and scope.